Effects of Various Drying Methods on the Quantity and Quality of Peppermint (Mentha piperita L.) Essential Oil - Mahya Ghorbani; Zahra Movahedi; Azizollah Kheiry *; Majid Rostami (Lorestan University of Medical Sciences, 2020)
Background and Aim: The quality of medicinal plants could be affected by different factors such as drying methods. Peppermint (Mentha piperita L.), which is native to the Mediterranean region, is cultivated for food, pharmaceutical and perfumery uses throughout the world. The aerial part of peppermint contains essential oil, phenolic and flavonoid compounds, fatty acids, vitamins, minerals, and salicylic acid. Materials and Methods: The impact of the drying process on the essential oil of peppermint was evaluated in an experiment with a much-randomized design using four treatments (oven drying at 40 and 50oC, shade and semi-shade drying) and three replications. The measured parameters included dry weight and oil quality as well as quantity. Results: According to the results, different drying methods had remarkable impacts on the investigated parameters at P<1%.  The results indicated that the highest dry weight and essential oil content were obtained from the semi-shade drying method. While drying at 50oC showed the maximum total menthol, the maximum p-Menthone, dl-Limonene, and Pulegone, Piperitone were obtained from the shade-drying method, and the maximum alpha-pinene, Sabinene, Menthofuran,1,8-Cineole, and trans-Caryophyllene were related to the shade-drying method, and the maximum β-pinene, menthyl acetate, and neo-Menthol were obtained from drying at 40oC. Conclusion: Overall, the results of the present experiment showed that the highest amounts of essential oil contents were obtained from shade and half-shade methods.